1985
DOI: 10.1128/iai.47.1.234-241.1985
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of Yersinia pestis within macrophages and an effect of the loss of the 47-megadalton plasmid on growth in macrophages

Abstract: The survival and growth of Yersinia pestis cells within mouse peritoneal cavities and within mouse peritoneal macrophages maintained in vitro was examined. Two strains were used which differed only in that one (KIM) contained the 47-megadalton plasmid associated with virulence and the second (KIM1) lacked this plasmid. The KIM cells, but not the KIM1 cells, acquired some resistance to phagocytosis during growth at 37°C which was not evident when cells were grown at 26°C. Whether previously grown at 26 or 37°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…Y. pestis is able to survive and replicate in murine macrophages in vitro (5,6,18,35,36,44) and in vivo (23) and is therefore classified as a facultative intracellular pathogen. Microscopic examination of tissues of animals experimentally infected with Y. pestis has shown the presence of plague bacilli inside macrophages (11,23,25,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Y. pestis is able to survive and replicate in murine macrophages in vitro (5,6,18,35,36,44) and in vivo (23) and is therefore classified as a facultative intracellular pathogen. Microscopic examination of tissues of animals experimentally infected with Y. pestis has shown the presence of plague bacilli inside macrophages (11,23,25,50).…”
mentioning
confidence: 99%
“…Early work on the trafficking of Y. pestis-containing vacuoles (YCVs) in primary murine macrophages yielded evidence that YCVs fuse with lysosomes (6,45). It was therefore suggested that Y. pestis survives in a phagolysosome (45).…”
mentioning
confidence: 99%
“…12,13 Further, in vivo studies showed that, in the early steps of Y. pestis infection, plague bacilli are predominantly detected in the macrophage population. 14,15 The infected macrophages provide a protected environment in which the pathogens can proliferate and synthesize their capsular and other virulence determinants, which enable the bacteria to acquire resistance to phagocytosis and to rapidly multiply outside of the host cells, once released into the extracellular environment. It is anticipated that the study of the interaction between Y. pestis and macrophages will lead to better overall understanding of how Yersinia subverts the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to phagocytosis is an important factor in the pathogenicity of Yersinia organisms; the existence of this factor stimulates infectivity and this brings about an infectious disease called yersiniosis (38)(39)(40)(41)53). It has been shown that the resistance of Yersinia organisms to phagocytosis depends on outer-membrane proteins encoded by virulence plasmids (6,7,10,36,47). When Yersinia organisms harboring virulence plasmids are incubated with macrophages taken from the mouse peritoneal cavity, growth of the bacteria stops for a while.…”
Section: Discussionmentioning
confidence: 99%
“…When Yersinia organisms harboring virulence plasmids are incubated with macrophages taken from the mouse peritoneal cavity, growth of the bacteria stops for a while. The bacteria resist phagocytosis by macrophages by secreting outer-membrane proteins and begin to multiply as soon as the activity of phagocytosis by macrophages decreases (10,36,43,44). However, the bacteria which do not secrete outer-membrane proteins resulting from a loss of plasmids cannot resist phagocytosis and finally loose their infectivity (10,36,43,44).…”
Section: Discussionmentioning
confidence: 99%